Mapping the Role of Corporate Entrepreneurship in Realizing Sustainable Business Based on SDGs (West Science Journal Economic and Entrepreneurship, 2025)
This study explores the role of corporate entrepreneurship in fostering sustainable business practices aligned with the Sustainable Development Goals (SDGs) through a qualitative analysis of five informants. Findings highlight that corporate entrepreneurship drives innovation, identifies sustainability opportunities, and supports risk-taking for long-term gains. However, challenges such as balancing profitability with sustainability, stakeholder misalignment, and resource constraints persist. The study emphasizes strategic approaches, including integrating sustainability into organizational visions, fostering cross-departmental collaboration, and engaging stakeholders to overcome these challenges. The findings contribute to the understanding of corporate entrepreneurship as a lever for achieving SDGs and provide actionable insights for practitioners and policymakers.